Individual differences in multi-tasking ability moderate the benefits of using low-degree automation. - Greenwell-Barnden, Jayden N.; Loft, Shayne; Bowden, Vanessa K.; Bender, Angela D.; Whitney, Susannah J.; Lipp, Ottmar V.; Visser, Troy A. W. (Theoretical Issues in Ergonomics Science, 2025)
Previous research has explored the effects of automation on task performance, situation awareness (SA), and workload, frequently finding that providing more automation is beneficial. However, studies rarely consider individual differences in cognition and how this may impact the effects of automation. This study investigated the impact of low-degree automation, and whether multi-tasking ability modifies its impact on the above outcomes. Two experiments were conducted with 216 undergraduate students. In Experiment 1, participants completed multi-tasking-based tasks to derive a multi-tasking index and engaged in a multi-tasking intensive air traffic control simulation under two conditions, manual and automated, applied to accepting and handing-off aircraft at the controlled airspace boundary where performance was assessed. SA was measured by Situation Present Awareness Method. Workload was measured objectively by latency to SA queries. Experiment 2 extended the findings by utilizing a similar methodology on a different automated-assisted subtask - aircraft conflict detection. Experiment 2 retained SA and workload measures with the addition of the NASA-TLX for subjective workload. In both experiments, poorer multi-taskers exhibited greater benefits from automation applied to acceptance and hand-off, improved conflict detection and reduced workload. Better multi-taskers had greater AA. This work underscores the importance of considering individual cognitive differences when designing automated systems.